Mengoptimalkan Mutu Pendidikan Agama Islam: Analisis Kebutuhan dan Strategi Efektif Pengawasan di Kabupaten Nganjuk - Lutfiatus Zuhroh (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy article comprehensively analyzes the problems of Islamic Religious Education (PAI) supervision and formulates effective strategies to improve the quality of education in Nganjuk Regency. The background of the problem indicates a structural imbalance between the number of PAI supervisors and the educational institutions they are supposed to supervise, resulting in low supervisory effectiveness. This imbalance is exacerbated by the delay in the appointment of new supervisors despite their qualifications, as well as the administrative implications for the payment of teacher professional allowances. This article uses a qualitative method with a descriptive analysis approach and USG analysis, as well as William Dunn's theory. Theoretically, this condition contradicts the concept of modern supervision, which emphasizes the role of supervisors as facilitators and instructional leaders. Limited resources and high workloads result in supervision tending to be sporadic and focused on administration rather than substantive development. These findings indicate the need for strategic policy interventions. Therefore, this article recommends three main strategies: 1) simplifying the bureaucratic process for appointing supervisors, 2) optimizing the allocation and workload of existing supervisors, and 3) developing a community-based supervision model. By implementing this strategy, it is hoped that the PAI supervision system in Nganjuk Regency can become more professional, effective, and sustainable, which will ultimately significantly improve the quality of PAI learning